Mild Cognitive Impairment and Dementia Involving Multiple Cognitive Domains in Mexican Urbanites. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Kulesza, Randy J; Torres-Jardón, Ricardo; Hernández-Luna, Jacqueline; Ávila-Cervantes, Rodrigo; Macías-Escobedo, Edgar; González-González, Oscar; González-Maciel, Angelica; García-Hernández, Kevin; Hernández-Castillo, Ariatna; Villarreal-Ríos, Rodolfo (J Alzheimers Dis, 2019)
Exposures to fine particulate matter PM2.5 and ozone O3 are associated with Alzheimer's disease (AD) risk. Mexico City residents have lifetime exposures to PM2.5 and O3 above annual USEPA standards and their brains contain high redox, combustion, and friction-derived magnetite nanoparticles. AD pathological changes with subcortical pre-tangle stages in infancy and cortical tau pre-tangles, NFT Stages I-II, and amyloid phases 1-2 are identified by the 2nd decade. Given their AD continuum, a reliable identification of cognitive impairment is of utmost importance. The Montreal Cognitive Assessment (MoCA) was administered to 517 urbanites, age 21.60±5.88 years, with 13.69±1.28 formal education years, in Mexican PM2.5 polluted cities. MoCA score was 23.92±2.82, and 24.7% and 30.3% scored ≤24 and ≤22, respectively (MCI≤24, AD≤22). Cognitive deficits progressively targeted Visuospatial, Executive, Language, and Memory domains, body mass index (BMI) impacting total scores negatively (p = 0.0008), aging driving down Executive, Visuospatial, and Language index scores (p <  0.0001, 0.0037, and 0.0045), and males performing better in Executive tasks. Average age for AD MoCA scores was 22.38±7.7 years. Residency in polluted cities is associated with progression of multi-domain cognitive impairment affecting 55% of Mexican seemingly healthy youth. Normal BMI ought to be a neuroprotection goal. MoCA provides guidance for further mandatory neuropsychological testing in young populations. Identifying and lowering key neurotoxicants impacting neural risk trajectories in the developing brain and monitoring cognitive performance would greatly facilitate multidisciplinary early diagnosis and prevention of AD in high risk young populations. Cognitive deficits hinder development of those representing the force moving the country in future years.